Consolidated and Undrained Ring Shear Tests on the Sliding Surface of the Hsien-du-shan Landslide in Taiwan - Hung-Ming Lin; Jian-Hong Wu; Erik Sunarya (Geofluids)
A new consolidated undrained ring shear test capable of measuring the pore pressures is presented to investigate the initiation mechanism of the Hsien-du-shan rock avalanche, triggered by Typhoon Morakot, in southern Taiwan. The postpeak state of the landslide surface between the Tangenshan sandstone and the remolded landslide gouge is discussed to address the unstable geomorphological precursors observed before the landslide occurred. Experimental results show that the internal friction angle of the high water content sliding surface in the total stress state, between 25.3 and 26.1°, clarifies the reason of the stable slope prior to Typhoon Morakot. In addition, during the ring shear tests, it is observed that the excess pore pressure is generated by the shear contractions of the sliding surface. The remolded landslide gouge, sheared under the high normal stress, rendered results associated with high shear strength, small shear contraction, low hydraulic conductivity, and continuous excess pore pressure. The excess pore pressure feedback at the sliding surface may have accelerated the landslide.